Pemanfaatan Na2O/Fe3O4 Sebagai Katalis Pada Tahap Tansesterfikasi Sawit Off Grade Menjadi Biodiesel - Trisuciati Syahwardini; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Off-grade palm oil is a source of vegetable oils that utilization is not maximized yet. It has ALB > 2% so must be process with esterification and transesterification. In general, biodiesel is produced through transesterification reactions using homogeneous catalysts. Homogeneous catalysts can be replaced with heterogeneous catalysts with easily separated and environmentally friendly. Waste iron powder can be used as catalyst support and provide metallic properties for separate product easily. This study aims to create a catalyst that has metallic properties and to study the transesterification reaction process conditions at transesterification process. Esterification process were reacted at 60 °C with time reaction 1 hour, molar ratio of methanol : oil of 12:1 and 1% H2SO4-w catalyst. The esterification reaction can reduce levels of ALB from 11.95% to 1.44%. Transesterification conducted with the molar ratio of methanol : oil in a row are 6:1, 8:1, and 10:1, the amount of catalyst modification 1% -w, 2%-w, 3% -w, a reaction temperature of 50 °C, 60 °C , 70 °C, and the reaction time 3 hours. Processing data using Response Surface Methodology (RSM), while the number of experiment are determined by Central Composite Design (CCD). Yield was resulted in ranging from 22.34% to 59.92%. The highest yield obtained at 60 °C with molar ratio of methanol : oil is 8:1 and the amount of catalyst Na2O/Fe3O4 2%-w.Keywords : biodiesel, heterogeneous catalyst, off-grade palm, rsm, transesterification.